Correction of Excessive Tibial Plateau Angle and Limb Shortening in a Juvenile Dog Using a Hinged Circular Fixator Construct and Distraction Osteogenesis - Daniel D. Lewis; Stanley E. Kim; Justin Shmalberg; Sandra L. MacArthur (Case Reports in Veterinary Medicine)
An 18-week-old Rhodesian Ridgeback puppy that was hit by a car sustained a Salter-Harris type III fracture of the left proximal tibial physis and ipsilateral diaphyseal femoral and tibial fractures. The diaphyseal fractures were successfully stabilized with bone plate fixation. Premature closure of the caudal aspect of the proximal tibial physis, secondary to the proximal physeal fracture, resulted in an excessively high tibial plateau angle (TPA) of 50° with a limb length discrepancy of 13% by 24 weeks of age. The deformity was addressed by performing a proximal tibial osteotomy and subsequent distraction osteogenesis to reduce the TPA while concurrently lengthening the crus. A radial osteotomy was performed in the proximal metaphyseal region and the hinged fixator was applied. Distraction was initiated the day following surgery at a rate of 1 mm per day as measured along the caudal cortex of the tibia with a rhythm of three distractions daily. Distraction was terminated 19 days postoperatively. Sequential distraction of the osteotomy resulted in 17 mm of tibial lengthening and a final TPA of 3°. The fixator was removed 52 days after application. Complications included wire tract inflammation involving the wires securing the proximal segment and a calcaneal fracture which required bone plate stabilization. The left pelvic limb was only 8% shorter than the right pelvic limb and the dog had only a subtle lameness 12 months after surgery. The hinged circular fixator construct allowed for both the reduction of the TPA and limb segment lengthening in this dog.